Improving Public Employment Services Through Partnerships with Non-Public Providers : Synthesis of International Experience and Implications for Kosovo - Hiebl, Julian (World Bank, Washington, DC, 2020)
Rapidly changing labor markets are affecting the service delivery model of Pubic Employment Agencies (PEAs). PEAs in Europe and beyond have come to adopt more comprehensive and client-centric services to satisfy the increasing needs of jobseekers and firms. In addition to expanding their range of services, PEAs have also become subject to increasing demands to improve their quality and efficiency. PEAs around the world are responding to increased demands by engaging in different types of partnerships. Besides collaboration with other public bodies, partnerships with non-public labor market actors such as private employment agencies, private training providers, and NGOs have become an increasingly important instrument for PEAs to increase coverage, quality, and efficiency of services. The main advantages of partnerships relate to improved exchange of information, better access to external expertise, as well as greater innovation and flexibility. International experience suggests that PEAs mainly benefit from better exchange of labor market information, access to a larger pool of vacancies and CVs, as well as flexibility and efficiency gains through contracting out employment services, training and other active measures to external providers. The Public Employment Agency of Kosovo can strongly benefit from engaging in partnerships with non-public providers. Kosovo’s employment policy framework acknowledges the role of non-public providers in delivering services. Given the limited experience with partnerships so far, however, it is important to follow a “learning by doing” approach that allows for the piloting and adequate sequencing of partnership arrangements while building capacity to manage such partnerships along the way.